DOI: 10.11606/t.6.2017.tde-17042017-083842
|View full text |Cite
|
Sign up to set email alerts
|

Internações hospitalares e mortalidade por intoxicação medicamentosa em São Paulo

Abstract: Autorizo a reprodução e divulgação total ou parcial deste trabalho, por qualquer meio convencional ou eletrônico, para fins de estudo e pesquisa, desde que citada a fonte. DEDICATÓRIADedico meu trabalho aos doutorandos que vieram antes de mim e aos que virão. Pessoas que têm sonhos e anseios muitas vezes incompreendidos de trazer uma contribuição para a ciência e para a sociedade. Que se alegram em aprofundar seus conhecimentos sobre um objeto de estudo e trazer à tona resultados que, potencialmente, podem sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
2
0
6
Order By: Relevance
“…These differences, based on the specifications of the instructions, do not characterize failure of the technique employed and are in accordance with the study of Rosenblit et al (16) who found a difference of 0.6 g/dL between two automated techniques. Research carried out in Northern England, employing the copper sulphate precipitation technique to screen blood donors also observed differences between tests of 0.24 for men and 2.8 for women (17) . It is recommended that the variations should not exceed 0.3 g/dL when employing the cyanmethemoglobin method (18) .…”
Section: Discussionmentioning
confidence: 99%
“…These differences, based on the specifications of the instructions, do not characterize failure of the technique employed and are in accordance with the study of Rosenblit et al (16) who found a difference of 0.6 g/dL between two automated techniques. Research carried out in Northern England, employing the copper sulphate precipitation technique to screen blood donors also observed differences between tests of 0.24 for men and 2.8 for women (17) . It is recommended that the variations should not exceed 0.3 g/dL when employing the cyanmethemoglobin method (18) .…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory investigation was performed using selective and diagnostic tests such as the filter paper solubility test (20) , osmotic resistance test in 0.36% saline (21) , erythrocyte morphology (22) and alkaline electrophoresis in cellulose acetate at pH 8.6 (23) . Positive results were confirmed by acid electrophoresis in agarose gel (24) ; hemoglobin (Hb) A 2 (23) was measured when the beta thalassemia trait was suspected and intra-erythrocyte Hb H testing was performed when electrophoresis was positive (25) .…”
Section: Methodsmentioning
confidence: 99%
“…Diante disto, muitos deles tornam-se contestadores, impulsivos e agressivos, mas ao mesmo tempo imaturos e inseguros . Essa mistura de sentimentos causam angústia, tristeza e medo, que se não forem adequadamente manejados, podem levar à dependência química Sendo o suicídio um problema de saúde pública previnível torna-se imperativo a criação de campanhas de informação sobre esse assunto, que ainda é considerado um tabu na sociedade atual (OLIVEIRA, 2017). Além disso, é importante que as autoridades em saúde promovam a sensibilização e capacitação de profissionais de saúde de todos os níveis de atenção com vistas à detecção precoce de pacientes com ideação suicida (CARVALHO et al, 2017).…”
Section: As Variáveis Sociodemográficas Associadas Especificamente àS...unclassified